Nuevos materiales bioorgánicos de actividad antitumoral - Hernández Gorritti, Wilfredo Román (2015)
rhernand@ulima.edu.pe; mlcacere@ulima.edu.pe; fccarras@ulima.edu.pe; abraham.vaisberg@upch.pe; espodine@ciq.uchile.cl; jmanzur@ing.uchile.cl; hennig@chemic. uni-leipzig.de; sieler@uni-leipzig.de; beyinorg@uni-leipzig.de